Power, Protection and Magic in Thailand The Cosmos of a Southern Policeman - Reynolds, Craig J. (ANU Press, 2019)
This biographical study of an unusual southern policeman explores the relationship between religion and power in Thailand during the early twentieth century when parts of the country were remote and banditry was rife. Khun Phan (1898-2006), known as Lion Lawman, sometimes used rather too much lethal force in carrying out his orders. He was the most famous graduate of a monastic academy in the mid-south, whose senior teachers imparted occult knowledge favoured by fighters on both sides of the law. Khun Phan imbibed this knowledge to confront the risks and uncertainty that lay ahead and bolster his confidence and self-reliance for his struggle with adversaries. Against the background of national events, the story is rooted in the mid-south where the policeman was born and died. Based on a wide range of works in Thai language, on field trips to the region and on interviews with local and regional scholars as well as the policeman's descendants, this generously illustrated book, accompanied by short video clips, brings to life the distinctive environment of the lakes district on the Malay Peninsula.